Forest carbon payments: A multidisciplinary review of policy options for promoting carbon storage in EU member states - Assmuth, Aino; Autto, Hilja; Halonen, Kirsi-Maria; Haltia, Emmi; Huttunen, Suvi; Lintunen, Jussi; Lonkila, Annika; Nieminen, Tiina M.; Ojanen, Paavo; Peltoniemi, Mikko; Pietilä, Kaisa; Pohjola, Johanna; et al. (Elsevier, 2024)
Forest carbon sinks can play an important role in mitigating climate change, but currently only a few policies exist globally where economic incentives are created for forest owners to maintain and strengthen sinks. This article aims to facilitate the design and implementation of governmental payment schemes for forest carbon uptake services by presenting a multidisciplinary analysis of the many challenges involved in such schemes and by proposing potential solutions. We assess the consequences, opportunities, and risks of carbon payment schemes from economic, ecological, social, and legal points of view based on existing literature. Our analysis is set in the context of the European Union (EU), but many of the central findings have relevance for a broader geographical area. The main economic challenges of implementing carbon payment schemes relate to potential leakage, the question of additionality, and uncertain forest-owner behavior. The most important ecological considerations include effects on soil carbon dynamics and biodiversity as well as issues of non-permanence and forest resilience. Our exploration of the social acceptance of carbon payments among the general public, key market actors such as forest owners and forest industry, and other stakeholders suggest that both the process of developing the scheme and its details are significant. Further, our legal analysis indicates that central challenges for carbon payment schemes within the EU rise from the requirement to comply with competition and state aid regulations. Finally, we synthesize our findings and suggest a two-step approach for introducing public carbon payments in an EU member state. Initially, the scheme could be launched via De minimis aid or the new aid scheme (GAFSRA). A low carbon price could be applied to moderate market effects, and the payments could be limited to additional carbon storage only. Peatlands, where tradeoffs exist between tree biomass carbon and soil carbon, should initially be excluded from the standard payment scheme, and regulated with command-and-control instruments and measure-based payments instead. In the future, an improved knowledge base and institutional changes may enable schemes that encompass all ecosystem carbon pools on all relevant soil types and create optimal incentives for both forest management and land-use choices by pricing all land-based sinks and emissions. Such schemes could utilize, e.g., cap-and-trade instruments and be complemented by import tariffs to control carbon leakage.
Keywords: carbon payment scheme; forest carbon; additionality; carbon leakage; social acceptance